Strategies for Sustaining Joint Forest Management - Lessons from Tamil Nadu Afforestation Project, India - Sreedharan, C. K.; Matta, Jagannadha Rao (Indian Forester, 2007)
Joint Forest Management (JFM), a co-management programme between government Forest Departments and local people, has been hailed as a successful strategy in arresting forest degradation and promoting socio-economic development of forest fringe villages in India. Sustaining the programme, however, was found to be a major challenge in the absence of lasting institutional mechanisms and regular income flow to the participating communities. The Tamil Nadu Afforestation Project (TAP) addressed these challenges by focusing on (i) providing stronger rights and responsibilities for local forest management, (ii) developing specific institutional measures toward empowering rural poor and women, (iii) ensuring improved sectoral integration and flow of additional developmental assistance, and (iv) promoting flexible and effective programme implementing organizations and stakeholder capacities. These approaches and their outcomes are discussed in the paper.